Some optical, magnetic and transport properties of CdMoO4:Nd3+. Issue 3 (15th February 2016) - Groń, T.; Tomaszewicz, E.; Berkowski, M.; Sawicki, B.; Urbanowicz, P.; Kusz, J.; Duda, H.; Oboz, M.
Abstract: Single crystal of new cadmium and neodymium molybdate solid solution (Cd0.958 Nd0.028 □0.014 MoO4, where □ denotes cationic vacancies) has been successfully grown by the Czochralski method. The X-ray diffraction analysis confirmed that this solid solution crystallizes in the scheelite type structure, the Nd 3+ ions do not show long-range order and they are randomly distributed in the unit cell, substituting the Cd 2+ ions. As a consequence, the unexpected properties of CdMoO4 :Nd 3+ are observed such as the energy gap (~1.77 eV) twice smaller than that of the matrix CdMoO4, a paramagnetic state with the short-range ferromagnetic interactions, behavior related to the electrical conductor with p – n transition along the 〈100〉 axis, the semiconducting behavior with n – p transition along the 〈001〉 axis and the diode-like behavior found to be of Schottky- or Maxwell-Wagner type. Therefore, we predict great potential of this single crystal for technical applications in electronic devices.